The Influence of Vocabulary Knowledge on Reading Comprehension Achievements - LARABA, Samir (Journal of Human Sciences, 2010)
We can never overstate the power of words. Perhaps the greatest tools we can give students, not only in their education but more generally in life, is a large, rich vocabulary. This research reports on the importance of vocabulary to reading achievement. Providing vocabulary instruction is one of the most significant ways in which teachers can improve students’ reading comprehension. Readers cannot understand what they are reading without knowing what most of the words mean. A large vocabulary is more specifically reflective of high levels of reading achievement.